Differences in the functional connectivity density of the brain between individuals with growth hormone deficiency and idiopathic short stature. (May 2019) - Hu, Yumin; Liu, Xiaozheng; Chen, Xiaojun; Chen, Tao; Ye, PeiPei; Jiang, Lezhen; Fu, Yuchuan; Xie, Xiaoling; Shan, Xiaoou; Yan, Zhihan
Highlights: The functional connectivity density was investigated between the subjects with idiopathic short stature and growth hormone deficiency. The GHD group exhibited significantly decreased FCD in the left postcentral gyrus, right precentral gyrus and left cerebellar lobes 7b and 6. The FCD value of the left postcentral gyrus in subjects with ISS positively correlated with IGFBP-3 levels and was somewhat correlated with IGF-1 levels. The impact of GHD on brain network mainly involved the somatosensory, somatic motor and cerebellum network. Abstract: Purpose: The aim of the present study was to investigate the differences in the topological organization of functional brain networks between children with growth hormone deficiency (GHD) and those with idiopathic short stature (ISS). Methods: Thirty-one children with GHD and fifty-three children with ISS were recruited based on the results of GH stimulation tests. Resting-state fMRI data were acquired from all children. Whole brain functional connectivity density (FCD) analysis and subsequent seed-based functional connectivity analysis were used to explore the differences in functional brain networks between the children with ISS and GHD. Correlation analyses among the results of clinical laboratory examinations, neuropsychological scales and FCD values of different brain regions were applied. Results: Compared with the ISS group, the GHD group exhibited significantly decreased FCDs in the left postcentral gyrus, right precentral gyrus and left cerebellar lobules 7b and 6. The subsequent functional connectivity analysis found decreased functional connectivity between lobules 7b and 6 of the left cerebellum as well as the left postcentral gyrus and right precentral gyrus in the GHD group compared to that in the ISS group. In addition, the FCD values of region 6 of the left cerebellum in the GHD group were negatively correlated with the scores on the Symptom Checklist-90 and Eysenck Personality Questionnaire. The FCD value of the left postcentral gyrus in children with ISS positively correlated with IGFBP-3 levels and was approximately correlated with IGF-1 levels. Conclusions: These findings highlight the impact of growth hormone deficiency on the brain network that mainly involves the somatosensory, somatic motor and cerebellum networks, which may contribute to the behavioural problems observed in these children.